2010
DOI: 10.1017/s1751731109990875
|View full text |Cite
|
Sign up to set email alerts
|

Short-term behavioural effects of weaning age in outdoor-reared piglets

Abstract: Age at weaning affects the behaviour of piglets weaned in conventional confined environments. The adaptation of piglets to this event, which exposes piglets to important stressors, has not been examined in detail in outdoor systems. The aim of this study was to compare the behaviour of piglets weaned at 3 or 4 weeks of age in an outdoor production system. Six replicates of four piglets born and raised outdoors, originated from different litters but previously acquainted, were weaned at the age of approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
3
6
1
2
Order By: Relevance
“…Overall, the post-weaning behavioural response observed in this study corroborate several studies that conclude that early and abrupt weaning is a source of distress for young piglets (Weary et al, 1999;Colson et al, 2006;Hö tzel et al, 2010). In addition, this suggests that handling quality may contribute to aggravate the distress response to weaning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the post-weaning behavioural response observed in this study corroborate several studies that conclude that early and abrupt weaning is a source of distress for young piglets (Weary et al, 1999;Colson et al, 2006;Hö tzel et al, 2010). In addition, this suggests that handling quality may contribute to aggravate the distress response to weaning.…”
Section: Discussionsupporting
confidence: 88%
“…Early-weaned piglets usually display behavioural responses indicative of distress, such as increased frequency of vocalisations (Weary et al, 1999;Colson et al, 2006), abnormal behaviours (Gonyou et al, 1998;Weary et al, 1999;Worobec et al, 1999), aggression (Jarvis et al, 2008;Devillers and Farmer, 2009), escape attempts (Worobec et al, 1999;Hö tzel et al, 2010) and low-feed intake (Gonyou et al, 1998;Van der Meulen et al, 2010), which is accompanied by impaired intestinal integrity and functionality, growth depression, increased susceptibility to disease and mortality (Pluske et al, 1997;Van der Meulen et al, 2010). These responses are attributed to the early and abrupt separation from the dam and change in diet, although it is recognised that pre-and post-weaning environmental stressors may also contribute (Weary et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The behavioural response of piglets immediately after weaning, which was characterized by low feed intake and an increase in activityrepresented mainly by escape attempts and less time lying, and an increase in vocalizations -is in accordance with previous studies that concluded that many factors of weaning management underlie the behavioural response to weaning, such as changes in the physical and social environment (HÖTZEL et al, 2011), age at weaning (HÖTZEL et al, 2010) and quality of handling (SOMMAVILLA et al, 2011). Complementing this information, the present study demonstrates that intrinsic factors of individual piglets, associated to teat order, influence this response.…”
Section: Discussionsupporting
confidence: 89%
“…According to Table 2 Animal behaviors observed during the nursery phase and their definitions. Source: Adapted from Hurnik et al (1995), Hötzel et al (2004Hötzel et al ( , 2010 and Reiners et al (2010).…”
Section: Discussionmentioning
confidence: 99%